Hydrological Observation of Qiantang River in the River Crossing Tunnel of Metro Line 8. Issue 1 (July 2020) - Zhou, Hanyu; Dong, Haiyang; Lu, Hanzhang; Li, Zongyu; Chen, Fanjun
Abstract: Observation on hydrological characteristics and sediment concentration were conducted in this research, and data analysis and summary were carried out on vertical tidal current flow and vertical sediment concentration. The hydrological and sediment environment of Qiantangjiang Metro Line 8 river-crossing channel was investigated.